Mexico’s Higher Education Students’ Experience During the Lockdown due to the COVID-19 Pandemic - Zapata-Garibay, Rogelio; González-Fagoaga, Jesús Eduardo; Meza-Rodríguez, Elsa B.; Salazar-Ramírez, Edgar; Plascencia-López, Ismael; González-Fagoaga, Clara Judith (Frontiers in Education, 2021)
Transition from face-to-face to remote courses in Mexico represented a challenge for teachers, students, and parents from all education levels. The Mexican federal government declared phase two of the plan to reduce COVID-19 spread on March 24, 2020. In some states, mobility restriction measures started by March 17 included the education system. On April 13, educational activities began in the remote mode exclusively, and this situation could be extended until the end of the 2020–2021 cycle, if health conditions do not improve. Universities, teachers, and students were not ready to implement the emergency remote teaching (ERT) strategy because of the limited conditions of technological adaptation and digital connectivity in the country. The purpose of this cross-sectional study is to investigate the experiences of graduate and undergraduate students concerning the change from face-to-face to the ERT modality in the health emergency context due to the COVID-19 outbreak. We collected data from 660 students from 38 universities and 22 states across the country. The study investigated students' previous experience with online courses, technological tool use, barriers faced during the new teaching–studying modality, current use of educational and specialized tools, and some physical and mental health indicators. As a result, we found problems related to time management of their work activities, the balance of time between home and school activities, and perception about studying days, which they felt strenuous. More than half of all students reported Internet connection problems. Students from private universities declared a higher use of technological tools. Students from public universities expressed more significant difficulties following teachers' instructions, perceived less attention from teachers, considered the change to remote courses was difficult, and felt overwhelmed by the required technological skills. Students in the first two years of university reported a higher proportion having deemed the most strenuous study days and having had difficulties following the teachers' instructions and considered that the distance modality change was hard. Finally, all the students declared that the expenses increased in their home in the highest proportion were electricity, mobile phone data, and Internet service. Future research should focus on measuring the impact of ERT on students’ learning outcomes.